ANALISIS AZAS-AZAS UMUM PELAYANAN PUBLIK DI DINAS PERINDUSTRIAN DAN PERDAGANGAN KABUPATEN KERINCI: Eliyusnadi - M.Si, Eliyusnadi (Fakultas Ushuluddin Adab dan Dakwah Insitut Agama Islam Negeri Kerinci, 2020)
Analysis of General Principles of Public Service at the Industry and Trade Office of Kerinci Regency. Every community certainly really hopes for the existence of general principles of public services in providing services to the community, especially at the Kerinci Regency Industry and Trade Office. In order to provide satisfactory services to service users, service delivery must meet the general principles of good governance in order to create customer satisfaction, which is a measure of the success of a public service. The formulation of the research problem, namely, how are the general principles of public services at the Kerinci Regency Industry and Trade Service. The objective of the research is to find out the general principles of public services in the Kerinci Regency Industry and Trade Service. This research uses a qualitative approach where data is obtained through field interview guides to 7 informants referring to 6 research indicators, namely 1. Transparency 2. Accountability 3. Conditional 4. Participation 5. Non-Discriminatory. 6. Balance of Rights and Obligations. The data obtained in the field were analyzed based on the classification of the informants' answers which were described in the results and discussion of the research which was then carried out by the interpretative researcher. It is known that the General Principles of Public Service at the Industry and Trade Office of Kerinci Regency, from the six research indicators, five indicators are well implemented, namely accountability, conditionality, participation, non-discrimination and balance of rights and obligations, while transparency indicators have not been maximally implemented. For this reason, the authors suggest that the General Principles of Public Service in the Kerinci Regency Industry and Trade Service can be improved so that they are more transparent in providing services to the community.